Science seminar: Managing risks and uncertainty for smallholder farmers - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
On 19 September 2012, Dr. Michael Carter gave a live-streamed science seminar entitled: "Managing risks and uncertainty for smallholder farmers". Dr. Carter gave an in-depth presentation at the latest live streamed science seminar held by the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS). He discussed how index-based insurance is moving forward as a viable policy alternative to insure farmers against risks, and shared research into the role and potential of index insurance in rural development. Learn more on our web site: http://ow.ly/rhTE7